A Vedantic view of 'The musical composition of Tyagaya and the dynamism of the mind / Purushothaman Anantham Shyamal - Purushothaman Anantham, Shyamal (2006)
This dissertation titled, ''A Vedantic view of the Musical Compositions of Tyagaya and the Dynamism of the Mind" consists of six chapters. The first chapter gives an introduction and overview of the study undertaken. It also deals with the rationale, objectives, methodology and review of reference literature. This chapter gives a background of Vedas, Sastras and Sangeetham, which are a source of spiritual and moral inspiration for all people. An introduction is given on the literary works of Saint Tyagaya. The second chapter deals explains the relationship of Tyagaya with Lord Rama .. He was a genius as a Composer. His kritis are simple, melodies and spiritual. His compositions have an enduring value and they sprang from the depths of his heart. He worshipped Lord Rama as his Ista Devada and composed kirthanas on Lord Rama. His compositions have made the Carnatic Sangeetham world majestic and brought solace to mankind. The third chapter inspires with Tyagaya's sacred kirthanas explaining the way to comprehend Brahman. The spiritual goal of life is to manifest the divinity within the mind. The perfection of the mind manifests good karma of the body. The good karmas attain the realization of the Atman. Tyagaya's compositions constitute a treasure of musicological wisdom and saintly utterances of Karma, Bhakti and Jnana. He professed attainment of mukti, liberation from bondage, through Sangeetha bhakti. Tyagaya's music contributes to the mind a higher state of vibration. The development of the Spiritual Wisdom is to understand the related Jnana of Creation, the matter, the Atman and the Brahman. The spiritual science and the metaphysical are therefore the extension of Quantum science, which is again the extension of physical science. There is sufficient evidence to show that the Jnana of the Vedas and the Sangeetha Sastras have certain cosmic intelligence, which interlinks to the mind. The cosmic mind conceives dynamism to comprehend the Atman. The fourth chapter explains the significance of Sangeetam, Sastram, jnana and bhakti. Tyagaya analyses the spiritual aspect of Nada Brahmam and the mechanism of Sangeetharn in the culturing the mind to the Satva level. The faithful practice of Karma, Bhakti and Jnana in a Nishkamia manner would manifest purity of mind. Tyagaya has revealed innumerable pathways (Sampradayas), for the aspiring souls to purify the mind. The physical journey of the Mind and the quantum nature of the Brain is the subject of ultimate significance. The fifth chapter encompasses selections of kritis of Tyagaya to prove the dynamism of the body, mind and Atman. The Vedanta of Tyagaya is an excellent intellectual and spiritual subject for the present society and can stimulate a better understanding of the spiritual questions relating to creation,matter, mind, li fe, death, Atman and Brahman. Quantum Science aJso looks up to Vedantic principles. The final chapter is the conclusion of this study after assessing the contribution of Tyagaya's philosophy towards the status of the dynamism of the mind. Findings from Tyagaya's life, his intuitions, his compositions, his music, his message, his devotion, his realization and his liberation are outlined.